Islamic moral judgement on abortion and its nursing applications: expository analysis - Mohamad Ismail, Mohamad Firdaus; Hashi, Abdurezak Abdulahi; Nurumal, Mohd. Said; Md Isa, Muhammad Lokman (Elsevier, 2017)
Health workers, like nurses are tasked to save the lives of their patients, however, there are instances in which health workers have to deal with difficult cases in taking a life, such as abortion. Scholars in the field of healthcare assert that abortion is morally justified if it is sought for health reasons. Nevertheless, there are a number of cases in which abortion is sought on other grounds other than health, such as the individual choice to do so. Can a nurse refuse to provide their professional service towards these people? This paper uses analytical and comparative methods to address ethical issues in abortion from the Islamic and conventional perspectives. Nursing implication: Since the nurses instruct and assist people in forming a decision as they engage in nursing care, utilising a comprehensive view of abortion based on Islamic sources would provide a foundation in Muslim perspectives as they interact with Muslim patients. The subject area to investigate the degree of knowledge among nurses regarding the Islamic moral judgement on this event is extremely recommended for future management